Objectively Measured Physical Activity and Progressive Loss of Lean Tissue in Older Japanese Adults: Longitudinal Data from the Nakanojo Study. Issue 11 (28th October 2013) - Shephard, Roy J.; Park, Hyuntae; Park, Sungjin; Aoyagi, Yukitoshi
<x xml:space="preserve">Abstract</x> Objectives To relate 5‐year lean tissue loss to habitual physical activity of elderly adults. Design Longitudinal. Setting Community of Nakanojo. Participants Community‐living Japanese aged 65 to 84 (200 men, 268 women). Measurements Daily 24‐hour pedometer/accelerometer data, collected continuously for 5 years, were categorized into activity quartiles. Bioelectrical impedance measurements of lean body mass were taken annually. A sarcopenia threshold was defined arbitrarily as an appendicular lean mass/height2 of more than 1 standard deviation below the mean for healthy young Japanese. Results Subjects with greater habitual physical activity retained a greater lean mass over the 5 years of observation. Controlling for baseline lean mass and age, final lean mass was greater for the third activity quartile (men and women with respective mean counts of 7, 800 and 7, 700 steps per day or mean duration of exercise at >3 metabolic equivalents (METs) of 20 and 17 minutes per day) than for the first and second quartiles. A multivariate‐adjusted proportional hazards model predicted that, over the 5 years, men and women in the two lowest activity quartiles (<6, 700 and <6, 800 steps per day) were 2.3 (95% confidence interval (CI) = 1.4–4.5) and 3.0 (95% CI = 1.9–3.4) times as likely, respectively, to be sarcopenic as those in the highest activity quartile (>9, 000 and >8, 400 steps per day). Likewise, men and women with less than 16 and less than 14 minutes per day, respectively, of activity of more than 3 METs were 3.0 (95% CI = 2.0–6.0) and 3.5 (95% CI = 2.1–6.3) times as likely to develop sarcopenia as those with more than 28 and more than 22 minutes per day. Conclusion After adjustment for potential confounders, the risk of developing sarcopenia was substantially lower in elderly people taking at least 7, 000 to 8, 000 steps per day or exercising for at least 15 to 20 minutes per day at an intensity greater than 3 METs. Clinicians should encourage seniors to get at least this volume of regular daily exercise.